2019
DOI: 10.5539/jas.v11n5p93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management on Yield and Quality of Basmati Rice Varieties

Abstract: A 2-year study conducted to determine the effect of integrated nutrient management on yield and quality of basmati rice varieties in non-traditional area with 54 plots in split plot design. Variety HUBR 10-9 produced 18.8% higher mean grain yield and superior quality parameters than HUBR 2-1. Mean milling, head rice recovery, amylose content and alkali digestion value noted higher with HUBR 10-9 by 4.1%, 4.1%, 8.5% and 15.1% over HUBR 2-1, respectively. Addition of 75% recommended dose of fertilizers with 25% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
5
3
0
1
Order By: Relevance
“…192.29 kg ha -1 . These results are in confirmation with finding of Raikar et al[23] and Kandeshwari & Thavaprakash[24], Jat et al[25].…”
supporting
confidence: 93%
“…192.29 kg ha -1 . These results are in confirmation with finding of Raikar et al[23] and Kandeshwari & Thavaprakash[24], Jat et al[25].…”
supporting
confidence: 93%
“…Similar results on rice yields due to the integrated application of chemical fertilizer and organic manures were reported by (Sharma et al, 2016;Singh et al, 2018;Tang et al, 2018). Sravan and Singh (2019) also found that the application of recommended nutrients in an integrated approach (75% RDF+25% FYM) enhanced rice grain yield. The results indicate that organic and inorganic based fertilizer along with lime had a more influential effect on rice grain due to the higher available nutrients and optimum soil properties.…”
Section: Yieldsupporting
confidence: 83%
“…Its increase or decrease combination with FYM and Biofertilizers. Same results also found by Sahu et al [2] Pandey et al [1] Farooq et al [3] Raj et al [4] Sravan and singh et al [5].…”
Section: Test Weightsupporting
confidence: 81%